Eggshell Powder (ESP) as low-cost adsorbent for wastewater treatment. Issue 1 (June 2021) - Arshad, M F; Zailani, W W A; Ismail, N; A Zainol, M R R M; Abdullah, M M A B; Tahir, M F M
Abstract: Filtration is the process where the solid particles are separated from the solution by passing it through porous pores. This process always comes together with the adsorption method and it depends on the type of filter media being used. Currently, activated carbon, zeolite and sand are widely used in treating wastewater influent. However, the increasing demands and materials cost had encouraged various approaches in finding solutions to replace the current filter media. Therefore, eggshell waste is introduced in this study as a replacement material for zeolite to treat wastewater impurities. The usage of eggshell waste as a new filter media is more beneficial which represents a low cost, renewable, available and sustainable approaches. Thus, this study revealed the optimum proportion of Eggshell Powder (ESP) as a filter media for wastewater treatment. The amount of eggshell used varies from 20%, 40%, 60% and 80% labelled as S3a, S3b, S3c and S3d respectively. The parameters examined were BOD, COD, SS, turbidity, colour, NH3-N, NO3-N, Fe and pH. This study had found that the most efficient filter media to replace zeolite is S80 media. S3d media was able to remove almost all the examined parameters with high percentage removal range between 40% to 90% removal. As a conclusion, this study hopes that by utilizing an industrial waste as a low-cost adsorbent, the environmental ecosystem can be protected for the sake of next generations.